2005
DOI: 10.1115/1.1929810
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Design of and Experimental Measurements in a Double-Passage Transonic Turbine Cascade Model

Abstract: A new transonic turbine cascade model that accurately produces infinite cascade flow conditions with minimal compressor requirements is presented. An inverse design procedure using the Favre-averaged Navier-Stokes equations and k‐ε turbulence model based on the method of steepest descent was applied to a geometry consisting of a single turbine blade in a passage. For a fixed blade geometry, the passage walls were designed such that the surface isentropic Mach number (SIMN) distribution on the blade in the pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Some researchers [13] indicated that the design of bleed slot was redundancy. And it leaded to serious difficulties in comparing numerical simulation to experiments [14].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers [13] indicated that the design of bleed slot was redundancy. And it leaded to serious difficulties in comparing numerical simulation to experiments [14].…”
Section: Introductionmentioning
confidence: 99%
“…Laskowski et al [16] designed a passage for a linear cascade experiment: they used a gradient-based optimization method to obtain an infinite cascade flow condition without the use of suction bleeds. The width of the passage was double-pitch and only a single-cascade blade was installed within the passage.…”
Section: Introductionmentioning
confidence: 99%
“…A passage for a linear cascade experiment was designed by using a gradient-based optimization method to obtain an infinite cascade flow condition without using suction bleeds (Laskowski et al 2005). The width of the passage is double-pitch and only a single cascade blade is installed within the passage.…”
Section: Introductionmentioning
confidence: 99%